2010
DOI: 10.1177/0886109910364356
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Women Versus Addressing Gender in Microcredit: Lessons From Honduras

Abstract: Microcredit, the practice of extending small loans to women who work in the informal economy, aims to help women achieve financial empowerment and independence. The research on microcredit, however, has tended to ignore how the context of women’s household relations can complicate this goal. This report of an ethnographic study of women’s participation in microcredit in Tegucigalpa, Honduras, indicates that male partners’ behaviors can both facilitate and limit women’s use of loans and repayment strategies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…A few older/middle-aged men (all married) also view WPD from this logical point of view. Vonderlack-Navarro (2010) revealed similar rational masculine patterns in Honduras, where some men have facilitated female participation in development initiatives.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…A few older/middle-aged men (all married) also view WPD from this logical point of view. Vonderlack-Navarro (2010) revealed similar rational masculine patterns in Honduras, where some men have facilitated female participation in development initiatives.…”
Section: Discussionmentioning
confidence: 67%
“…These findings are in line with those of Haque & Kusakabe (2005) ; Islam and Karim (2011–2012) ; Schuler et al (1998) ; and Yount et al (2016) , which describe married Bangladeshi men’s masculine identities as patriarchal and dominating. Another study conducted in Honduras ( Vonderlack-Navarro, 2010 ) depicted similar masculine traits whereby men hindered female participation in development. However, the present study further identifies that men can oppose women’s professional development/freedom when they are afraid of losing male authority.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In culturally diverse environments as the Caribbean region, one cannot assume identity politics such as race, class and gender do not configure into how resources are managed and distributed. In fact, in this study I found that gender is a more palatable topic for discussion and one can locate, with relative ease, solid research on the social, political and economic intersections between women and credit (Armendáriz and Roome 2008, Maclean 2010, Rankin 2001, Vonderlack-Navarro 2010. However, analyses of multiple identities -class, race, gender -that operate within the social economy are rare.…”
Section: Intersectionality and The Social Economymentioning
confidence: 77%
“…In reality, empowerment is often dependent on household dynamics, with husbands having the ability to facilitate or limit women's strategies for use of financial resources (Vonderlack-Navarro, 2010). In San Juan La Laguna, many women are widows having lost their husbands to either natural causes or the 30-year Guatemalan civil war that ended in 1996 (Green, 1995).…”
Section: Autonomymentioning
confidence: 99%